When personality pays: observer rating of personality and financial success of equity crowdfunded startups - Andrew Isaak; Julia Neuhaus; Denefa Bostandzic (Venture Capital, 2024)
This study investigates the value of third-party ratings of personality in investor pitches for predicting the investment intention and successful equity crowdfunding of U.S.-based startups. Based on 1175 ratings of 100 randomly selected investor pitch videos, we find that not only do investors' impressions of entrepreneurs Big Five personality traits predict investment intention but that several of these also predict entrepreneurs' actual crowdfunding success (particularly: openness, conscientiousness and extraversion). The study contributes to our knowledge of the links between (perceived) individual-level traits of the entrepreneur and their ability to finance a venture, a key challenge in the early stages of startups.
Keywords: M13; G41; D91; G24; D26; C31; C83; 650; Personality; Equity Crowdfunding; Big Five Personality Traits; Regression; Third Party Ratings; Investor Pitch; Venture Capital